Zmiany w podatku dochodowym od osób prawnych - Martynowicz, Aleksandra (Changes in Corporate Income Tax, 2009)
The changes in corporate income tax were introduced on November 6th 2008. The amendment contains a few regulations that are for the benefit of taxpayers. Some of the issues are new in the tax system, others are to complete existing regulations. The paper describes the characteristic of the most important changes, presents their influence on tax burden and shows their relevance to entrepreneurs. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 68-74